PENGARUH THIN CAPITALIZATION RULE PADA LEVERAGE PERUSAHAAN MASUK BURSA DI INDONESIA - Muhammad Rheza Ramadhan; Satria Agus Frandyanto; Riko Riandoko (Riset Akuntansi dan Keuangan Indonesia, 2017)
This research finds the effect of thin capitalization rule implementation to company leverage in Indonesia. This study used leverage data in 2015 (before the implementation) and 2016 (after the implementation). The data was processed using paired sample t-test. Based on hand-collected sample of 69 publicity- listed indonesian firms for the 2015 and 2016 year, our paired sample t-test result, descriptive statistic, and correlation test result show that thin capitalization rule can reduce company leverage by 73,8%. Keywords: thin capitalization, tax avoidance, tax aggressiveness, transfer pricing, leverage